TAFSIR MAQASHIDI PRESPEKTIF ABDUL MUSTAQIM - Ibrahim, Aji Muhammad; Bela, Farah Aisya (STAI Asy-Syukriyyah, 2023)
Tafsir maqashidi is one of the new genres in an attempt to interpret the verses of the Qur'an in the contemporary era. Tafsir maqashidi comes from the basis of maqashid sharia or maqashid of the Qur'an. Among the many people who are engaged in the world of maqashidi tafsir, we study the thought of maqashdi tafsir Abdul mustaqim. Abdul mustaqim explained his opinion, that, maqashdi tafsir is one of the climbing efforts in carrying out an interpretation of the Qur'an, so the existence of this maqashidi tafsir occupies as a complement, not delegating the method or effort of the previous tafsir approach, because later in the steps to approach maqashidi tafsir then still use maudhui tafsir. Abdul Mustaqim is known as an expert in maqashidi interpretation who has a uniqueness in the steps to study maqashidi interpretation.